The Risk Threshold for Hemoglobin A1c Associated With Albuminuria: A Population-Based Study in China - Lian, Hong; Wu, Hongshi; Ning, Jie; Lin, Diaozhu; Huang, Chulin; Li, Feng; Liang, Ying; Qi, Yiqin; Ren, Meng; Yan, Li; You, Lili; Xu, Mingtong (Frontiers in Endocrinology, 2021)
Abstract Background: Diabetic kidney disease (DKD) is a kind of common microvascular complication of diabetes. This study aims to explore the possible links between blood sugar level and albuminuria, providing the exact cut point of the “risk threshold” for blood glucose with DKD. Methods: The relationship between blood glucose and albuminuria was modeled using linear and logistic regression in the REACTION study cohorts (N= 8932). Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated by logistic regression model. Two-slope linear regression was used to simulate associations between blood glucose and ACR. Results: We found that the increase in ACR was accompanied by increased HbA1c, with a turning point at 5.5%. The positive correlation remained highly significant (P<0.001) when adjusted for age, sex, marital status, education, smoking status, drinking status, BMI, waistline, SBP and DBP. In subgroup analyses including gender, obesity, hypertension, and smoking habits, the relationship was significant and stable. Conclusions: We determined a risk threshold for HbA1c associated with albuminuria in a Chinese population over the age of 40. HbA1c ≥ 5.5% was positively and independently associated with ACR. These results suggest the necessity of early blood glucose control and renal function screening for DKD in at-risk populations.